2020
DOI: 10.1016/j.bbrc.2020.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA DNAH17-AS1 promotes tumorigenesis and metastasis of non-small cell lung cancer via regulating miR-877–5p/CCNA2 pathway

Abstract: Background: A growing number of studies have revealed that long noncoding RNAs (lncRNAs) can function as important oncogenes or tumor suppressors. This study aimed to investigate the regulatory role of lncRNA DNAH17 antisense RNA 1 (DNAH17-AS1) on non-small cell lung cancer (NSCLC) and the underlying molecular mechanisms. Methods: RT-PCR was used to examine the expression of DNAH17-AS1, miR-877-5p and CCNA2 in NSCLC specimens and cell lines. The diagnostic and prognostic values of DNAH17-AS1 expression in NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Hsa-miR-877 was found to be overexpressed in gastric cancer, and also antagonized the promoting effect of Substance P in the occurrence and progression of gastric cancer, suggesting that miR-877-5p could be a potential drug target [47] . Further, miR-877-5 has been reported to participate in gene regulation of competing endogenous RNA (ceRNA) mechanisms in multiple tumors, including cervical cancer, malignant gliomas, and non-small-cell lung cancer [48][49][50] . Yijun Yang et al showed that Hsa-miR-137 effectively induced apoptosis and diminished tumorigenicity in multiple myeloma [51] .…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-877 was found to be overexpressed in gastric cancer, and also antagonized the promoting effect of Substance P in the occurrence and progression of gastric cancer, suggesting that miR-877-5p could be a potential drug target [47] . Further, miR-877-5 has been reported to participate in gene regulation of competing endogenous RNA (ceRNA) mechanisms in multiple tumors, including cervical cancer, malignant gliomas, and non-small-cell lung cancer [48][49][50] . Yijun Yang et al showed that Hsa-miR-137 effectively induced apoptosis and diminished tumorigenicity in multiple myeloma [51] .…”
Section: Discussionmentioning
confidence: 99%
“…Continuing advances in the development of next-generation sequencing and transcriptomics suggest that the investigation of lncRNAs in the regulation of cancer has emerged as a potential research field [ 21 ]. Accumulating evidence shows that lncRNAs are involved in tumorigenesis and have the potential to be used as diagnostic and prognostic biomarker in a wide range of cancers [ 22 , 23 ]. Worldwide research has focused on identifying potential diagnostic and prognostic markers, which might predict survival outcomes accurately.…”
Section: Discussionmentioning
confidence: 99%
“…14 On the contrary, miR-761 acted as a promoter in NSCLC cell malignancy by regulating cell proliferation and aggressiveness. 15 Given the feasibility of the circRNA-miRNA-mRNA regulatory network in revealing the mechanism responsible for cancer progression, 16,17 we predicted the miRNA and mRNA associated with circPRH1-PRR4 through bioinformatics tools. As a result, we found miR-877-5p was able to bind to circPRH1-PRR4, and the member RAS oncogene family (RAB3D) carried the complementary sites of miR-877-5p.…”
Section: Introductionmentioning
confidence: 99%